Pengaruh Modal Usaha dan Inovasi Terhadap Keberhasilan Usaha Ukm Komunitas Pelopor Usaha Gresik (KPUG) Di Desa Giri, Kecamatan Kebomas, Kabupaten Gresik - Noba Sholahuddin; Mochamad Syafii; Muhammad Zainal Abidin (Jurnal Ekonomi dan Kewirausahaan Kreatif, 2020)
This study aims to examine and prove the influence of venture capital and innovation on the success of the business of the Gresik Pioneer Business Community (KPUG) Small and Medium Enterprises in Giri village, Kebomas sub- District, Gresik District. This study uses a quantitative research approach with multiple linear regression analysis. The number of samples sampled by 50 Small And Medium Enterprises and collecting data was done using the questionnaire method to obtain data. The results showed that Business Capital (X1) did not affect the success of Small and Medium Enterprises businesses in Giri Village. Then Innovation (X2) has a positive and significant effect on the success of Small and Medium Enterprises businesses in Giri Village. And variables of the Business Capital (X1) and Innovation (X2) variables simultaneously influence the Success of the Business of the Pioneer Business Gresik (KPUG) Small And Medium Enterprises in Giri Village. This is evidenced by the value of Fcount (4.773)> Ftable (4.04), the significance level of t 0.13 smaller than α = 0.05